2014
DOI: 10.3233/bmr-130422
|View full text |Cite
|
Sign up to set email alerts
|

Pain, fear of falling and stair climbing ability in patients with knee osteoarthritis before and after knee replacement: 6 month follow-up study

Abstract: It would be reasonable to consider that FOF control is potentially useful for preventing severe functional limitation in stair climbing for subsequent knee OA before and early after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Our results concur with previous studies that reported reduction of pain following physiotherapy in TKA [6,25,26]. Recently, Unver et al reported reduction of pain at 4 weeks post-surgery [27]. Similarly, Heiberg et al reported declines in VAS score at 3 months postoperatively, while no additional recovery further till 9 months [28].…”
supporting
confidence: 92%
“…Our results concur with previous studies that reported reduction of pain following physiotherapy in TKA [6,25,26]. Recently, Unver et al reported reduction of pain at 4 weeks post-surgery [27]. Similarly, Heiberg et al reported declines in VAS score at 3 months postoperatively, while no additional recovery further till 9 months [28].…”
supporting
confidence: 92%
“…Stair walking (ascending and descending stairs) is one of the most important and challenging activities of daily living required to maintain mobility and independence [ 1 ]. However, stair walking demands a variety of physical functions such as proper lower limb strength, joint range of motion, kinesthetic intelligence, and visual processing for safe and coordinated locomotion [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, this study found that preoperative stair descent time and age predicted postoperative stair descent time, and that TUG test scores, 6MWT performance, and the extensor and flexor torque of the operated and non-operated knees were also significantly associated with postoperative stair descent time. In terms of stair descending activity, patients who completed selfreported assessments indicated a greater fear of falling during stair descent than during stair ascent (26), and Whitehouse et al indicated that descending stairs was one of the most difficult tasks to complete (27). Another study reported that 6 months after TKA, up to 60% of respondents had moderate-to-extreme difficulty in descending stairs (26,28).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of stair descending activity, patients who completed selfreported assessments indicated a greater fear of falling during stair descent than during stair ascent (26), and Whitehouse et al indicated that descending stairs was one of the most difficult tasks to complete (27). Another study reported that 6 months after TKA, up to 60% of respondents had moderate-to-extreme difficulty in descending stairs (26,28). Thus, balance ability and the thigh muscle strength of both the operated and nonoperated sides, which have a significant effect on the ability to ascend stairs, can also be expected to have a significant impact on the ability to descend stairs.…”
Section: Discussionmentioning
confidence: 99%